Folate-Targeted PEGylated Magnetoliposomes for Hyperthermia-Mediated Controlled Release of Doxorubicin - Cintra, Emílio R.; Hayasaki, Tacio G.; Sousa-Junior, Ailton A.; Silva, Artur C. G.; Valadares, Marize C.; Bakuzis, Andris F.; Mendanha, Sebastião A.; Lima, Eliana M. (Frontiers in Pharmacology, 2022)
Doxorubicin (DOX) is a chemotherapeutic agent commonly used for the treatment of solid tumors. However, the cardiotoxicity associated with its prolonged use prevents further adherence and therapeutic efficacy. By encapsulating DOX within a PEGylated liposome, Doxil® considerably decreased DOX cardiotoxicity. By using thermally sensitive lysolipids in its bilayer composition, ThermoDox® implemented a heat-induced controlled release of DOX. However, both ThermoDox® and Doxil® rely on their passive retention in tumors, depending on their half-lives in blood. Moreover, Thermo-Dox® ordinarily depend on invasive radiofrequency-generating metallic probes for local heating. In this study, we prepare, characterize, and evaluate the antitumoral capabilities of DOX-loaded folate-targeted PEGylated magnetoliposomes (DFPML). Unlike ThermoDox®, DOX delivery via DFPML is mediated by the heat released through dynamic hysteresis losses from magnetothermal converting systems composed by MnFe2O4 nanoparticles (NPs) under AC magnetic field excitation – a non-invasive technique designated magnetic hyperthermia (MHT). Moreover, DFPML dismisses the use of thermally sensitive lysolipids, allowing the use of simpler and cheaper alternative lipids. MnFe2O4 NPs and DFPML are fully characterized in terms of their size, morphology, polydispersion, magnetic, and magnetothermal properties. About 50% of the DOX load is released from DFPML after 30 min under MHT conditions. Being folate-targeted, in vitro DFPML antitumoral activity is higher (IC50 ≈ 1 μg/mL) for folate receptor-overexpressing B16F10 murine melanoma cells, compared to MCF7 human breast adenocarcinoma cells (IC50 ≈ 4 μg/mL). Taken together, our results indicate that DFPML are strong candidates for folate-targeted anticancer therapies based on DOX controlled release.